INNOVATIVE APPROACHES TO TEACHING ENGLISH: ENGAGING THE NEXT GENERATION OF LEARNERS - Jumaniyazova Lobar Sirojiddin kizi (TADQIQOTLAR.UZ, 2024)
This article explores innovative approaches to teaching English, emphasizing methods that engage the next generation of learners. Traditional techniques often fall short in addressing the diverse needs of contemporary students. This study reviews recent advancements in educational technology, interactive classroom activities, and personalized learning strategies that enhance English language acquisition. Through a detailed analysis of these approaches, the paper highlights their effectiveness in fostering student engagement and improving learning outcomes. The findings suggest that integrating modern tools and methods can significantly transform English teaching, making it more relevant and effective for today's learners.